2015
DOI: 10.1093/hmg/ddv289
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine treatment ameliorates the skeletal phenotype of a mouse model of diastrophic dysplasia

Abstract: Diastrophic dysplasia (DTD) is a recessive chondrodysplasia caused by mutations in SLC26A2, a cell membrane sulfate-chloride antiporter. Sulfate uptake impairment results in low cytosolic sulfate, leading to cartilage proteoglycan (PG) undersulfation. In this work, we used the dtd mouse model to study the role of N-acetyl-l-cysteine (NAC), a well-known drug with antioxidant properties, as an intracellular sulfate source for macromolecular sulfation. Because of the important pre-natal phase of skeletal developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
(56 reference statements)
0
24
0
Order By: Relevance
“…A deep understanding of the molecular mechanisms of these disorders is crucial to ultimately pave the way for innovative therapies. Recently, significant advances in the development of therapeutic approaches for some disorders have been achieved with the aim of alleviating, preventing or modifying the disease progression [70,[98][99][100][101]. This progress has been made thank to deep phenotyping of in vitro and/or in vivo models that has allowed the identification of new molecules or already existing ones through a drug repositioning approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A deep understanding of the molecular mechanisms of these disorders is crucial to ultimately pave the way for innovative therapies. Recently, significant advances in the development of therapeutic approaches for some disorders have been achieved with the aim of alleviating, preventing or modifying the disease progression [70,[98][99][100][101]. This progress has been made thank to deep phenotyping of in vitro and/or in vivo models that has allowed the identification of new molecules or already existing ones through a drug repositioning approach.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the growth plate of the animal model demonstrated reduced chondrocyte proliferation due to altered Indian hedgehog (Ihh) signalling [68] and reduced phosphorylation of the pocket protein p130 that inhibits transcription factors of the E2F family leading to the block in the G1 phase of cell cycle progression [69]. Even if sulfate uptake from the extracellular environment is crucial for PG sulfation in chondrocytes, an alternative source of sulfate, namely intracellular thiol compounds, has been reported in the dtd mouse suggesting potential pharmacological approaches to DTD [70]. Recently an over activation of fibroblast growth factor receptor 3 (FGFR3) signalling has been described in a Slc26a2 knock-out mouse, an animal model of ACG1B and AO2.…”
Section: Skeletal Dysplasias Linked To Proteins Involved In Sulfate Mmentioning
confidence: 99%
“…Thus far, there has been no alternative therapy under investigation but to provide palliative care for viable ACG1B and AO2 newborns [46,47]. Drug intervention during pregnancy has been proved practical and effective to ameliorate the retarded skeletal development and rescue postnatal death in mouse models mimicking human chondrodysplasias [[77], [78], [79]]. To our best knowledge, we conducted the first preclinical study with NVP-BGJ398 in SLC26A2-related conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For CS and DS disaccharide composition, GAG aliquots were digested with chondroitinase ABC (AMSBIO, Abingdon, UK) (digesting chondroitin sulfate A, B and C) or chondroitinase ACII (Seikagaku Corp., Tokyo, Japan) (digesting chondroitin sulfate A and C). Each digest was labeled with 2-aminoacridone (Thermo Fisher Scientific, MA, USA) and analyzed by reverse phase HPLC as described previously [ 61 ]. The dermatan sulfate (chondroitin sulfate B) fraction was determined as disaccharide fraction undigestable by chondroitinase ACII vs. disaccharides digested by chondroitinase ABC.…”
Section: Methodsmentioning
confidence: 99%